Association of sanitary pads and clothing with vulvovaginitis - Bardin, Marcela Grigol; Giraldo, Paulo César; Pinto, Cristina Laguna Benetti; Piassaroli, Virgínia Pianissoni; Amaral, Rose Luce Gomes do; Polpeta, Nádia (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Vulvar occlusion and moisture buildup resulting from the use of sanitary pads, synthetic underwear and/or tight pants are considered risk factors for the development of vulvovaginitis (VV). However, this association is still poorly elucidated. Objective: To associate the use of sanitary pads and clothing with the presence of bacterial vaginitis (BV) and vaginal candidiasis (VC). Methods: Cross-sectional study aimed at analyzing the use of sanitary pads and clothing in 307 volunteers from 18 to 45 years old, with and without BV and/or VC. A questionnaire comprehending six domains was applied individually to the volunteers, in an outpatient gynecology clinic at a university hospital (University of Campinas, Brazil). This study analyzed three of six domains. Vaginal material was collected for microbiologic diagnosis of BV (Nugent criteria) and VC (Gram stain and culture of the fungus in Saboureaud). Exclusion criteria were: use of antibiotics within 15 days, history of cancer, positive HIV and/or syphilis and immunosuppressive disease. Statistical analysis were made with Fischer and chi-square tests, using the software EPI INFO 0.5. Significance level was set at p<0.05. Results: In total, 141 (46%) women were diagnosed with VV. The mean age was 32 (±6.8) years and most women were Caucasian (52%), had a steady partner (83%) and were using hormonal contraceptives (64.5%). Women with presence of VV used more panties made of synthetic fabric (10.6% x zero), had more menstrual cycles (72.3 x 55.4%) than those without VV (p<0.005 and p<0.0001) and showed patterns of sanitary pads similar to those without VV. Conclusion: Habits of usage of sanitary pads is not associated with the presence of VV. Presence of menstrual cycle and use of synthetic underwear have been related with greater frequency of VV.